Destination personality: how to make the metaphor simpler? - Lin, Naiqing; Roberts, Kevin R. (My University, 2019)
A well-established destination personality facilitates differentiation of destinations and helps to create emotional loyalty and increase repeat visitors. Although destination personality and brand marketing have become increasingly important, there is still a lack of applied research that simplifies the salient dimensions of destination personality. This study applies parsimony analysis to help establish the simplest possible determination of destination personality to identify the top destination personality traits of Kansas. Participants (N = 209) were recruited by an online marketing company, and descriptive statistics, Garrett ranking analysis, and Mann-Whitney U-tests were conducted. The top brand personalities of Kansas identified amongst all visitors included hardworking and reliable. Compared to first-time visitors, repeat visitors perceived Kansas as contemporary, outdoorsy, and less sincere.
Citation: Lin, N., & Roberts, K. R. (2019). Destination personality: how to make the metaphor simpler? Anatolia, 0(0), 1–12. https://doi.org/10.1080/13032917.2019.1588758
Keywords: Garrett Ranking; Rural Tourism; Emotional Loyalty; First-Time Visitors; Repeat Visitors; Destination Personality